A new species of Urocleidoides Mizelle & Price, 1964 from the gills of Schizodon nasutus Kner, 1858 (Characiformes, Anostomidae) in southeastern Brazil - Ebert, M. [UNESP]; Osaki-Pereira, M. M. [UNESP]; de León, G. Pérez-Ponce; Silva, R. J. [UNESP] (Cambridge University Press (CUP), 2024)
Based on an integrative approach, this study describes a new species of Urocleidoides infesting Schizodon nasutus in the Paranapanema River basin, Brazil. The new species can be distinguished from its congeners by specific morphological features, including the shape of the male copulatory organ and accessory piece, the ventral bar shape, and the shape and size of the hooks. Molecular analyses, particularly of the 28S rDNA gene, suggest a close relationship between the new species and Urocleidoides paradoxus. The phylogenetic and taxonomic arrangement of Urocleidoides is discussed, as the analyses of the 28S rDNA and COI mtDNA resolved the genus as non-monophyletic, with Diaphorocleidus, Rhinoxenus, and Cacatuocotyle nested within it. Additional morphological and molecular data of other congeneric species are required to investigate the phylogenetic position and classification of Urocleidoides. This study underscores the significance of using integrative approaches in understanding host–parasite associations and phylogenetic relationships, contributing to the description of the freshwater fish parasite biodiversity in South America, particularly in the Paranapanema river basin.
Keywords: 28S rDNA; COI mtDNA; Dactylogyridae; fish helminthology; Monogenea; South America